Effects of aspirin and omega-3 fatty acids on composite and subdomain scores from the NEI-VFQ-25 questionnaire: the ASCEND-Eye randomized controlled trial - Emily L. Sammons; Georgina Buck; Louise J. Bowman; William M. Stevens; Imen Hammami; Sarah Parish; Jane Armitage; on behalf of the ASCEND Study Collaborative Group (BMC Ophthalmology)
Abstract Background The double-blind, 2 × 2 factorial design, placebo-controlled ASCEND randomized trial compared the effects of 100 mg aspirin daily and, separately, 1 g omega-3 fatty acids (FAs) daily on the primary prevention of cardiovascular disease in 15,480 UK adults with diabetes. We report the effects of these randomized treatment allocations on scores derived from the National Eye Institute’s Visual Function Questionnaire-25 (NEI-VFQ-25) in a subset of participants involved in the ASCEND-Eye sub-study. Methods Ordinal data from the NEI-VFQ-25 were analyzed using proportional odds regression methods. A common odds ratio with a 95% confidence interval was used to interpret the average effect size of randomization to each study treatment on composite and subdomain scores from the questionnaire. Results Neither randomization to aspirin nor omega-3 FAs for 7.5 years significantly affected composite or subdomain scores from the NEI-VFQ-25. Conclusion Applying the NEI-VFQ-25 in ASCEND-Eye represents one of the largest surveys of vision-targeted health-related quality of life in people with diabetes. Further observational analyses of these data are planned, to identify the clinical and demographic characteristics associated with lower composite and subdomain scores in a diabetic population. Trial registration Eudract No. 2004–000991-15; Multicentre Research Ethics Committee Ref No. 03/8/087 (29th December 2003); ClinicalTrials.gov No. NCT00135226 (24th August 2005); ISRCTN No. ISRCTN60635500 (1st September 2005).